Mathematical modelling of thin layer drying process under open sun of some aromatic plants - Akpinar, E. Kavak (Elsevier Sci Ltd, 2006)
In this work, the sun drying behaviour of aromatic plants as parsley, mint and basil was investigated. Drying experiments were conducted for parsley, mint and basil grown in Elazig, Turkey. The constant rate period is absent from the drying curves. The drying process took place in the falling rate period. The drying data were fitted to twelve the different mathematical models. Among the models, the Modified Page (1) model for mint and basil leaves and the model given by Verma et al. for parsley leaves were found to best explain thin layer open sun drying behaviour of the aromatic plants. The performance of these models was investigated by comparing the determination of coefficient (R), reduced chi-square (R) and root mean square error (RMSE) between the observed and predicted moisture ratios. The effective diffusivity coefficient of moisture transfer of parsley, mint and basil leaves were found within the range of 10(-12) m(2) s(-1). (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: open sun drying; mathematical modelling; mint; parsley; basil